Minimasi waste pada proses produksi roti menggunakan metode value stream mapping di UMKM Massempo Bakery - Rasyid, Abdul; Teppo, Anisa Nurjana; Uloli, Hendra (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research was conducted on the MSME Massempo Bakery with the aim of identifying and minimizing waste in its production process. Waste that occurs in the production process can negatively impact production efficiency and effectiveness, such as increased production time, unnecessary costs, and decreased product quality. The method used in this research is Value Stream Mapping (VSM), which aims to map the value flow of the entire production process, identify value-added and non-value-added activities, and discover potential waste. The research results show that the main wastes identified include defects (product defects), waiting (waiting time), and motion (excessive movement). Through analysis using VSM, potential improvements were found in activities that do not add value. The implementation of improvements was carried out by combining several similar activities and reducing inefficient operating time. From the improvement of process activity mapping, the total time was reduced from 20776.51 seconds to 18659.95 seconds, resulting in a total time savings of 2116.56 seconds, which indicates a significant increase in efficiency.